A NEW CSR PARADIGM FOR STATE-OWNED ENTERPRISE IN INDONESIA - Anggun Fii Jannatin Jaatsiyah; Dini Widinarsih (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
After the Regulation PER-5/MBU/04/2021 of the Minister of State-owned Enterprises’ (Badan Usaha Milik Negara; BUMN) took effect, it formed a new Corporate Social Responsibility (CSR) paradigm for BUMN in Indonesia. This article can add insight into business people, academics, and the general public regarding the implementation of the CSR. This study uses a self-study type of literature study using the results of researchers' review from documents or legislation’s archives and the socialization of Corporate Social and Environmental Responsibility (Tanggung Jawab Sosial dan Lingkungan; TJSL) in the Ministry of BUMN. The findings describe the chronology of the development of CSR in BUMN from year to year which changes in terms of name and its arrangements according to the policies issued. The Regulation No. PER-5/MBU/04/2021 of the Minister of BUMN on TJSL can be a reference for CSR implementation in Indonesia because the benefits and pillars of the TJSL program are required in line with the aim of TPB / SDGs, so that the CSR’s concept paradigm that previously focused on profit allocation becomes a sustainable impact. The publication of the impact of the TJSL program is required to Article 27 of BUMN PER-5/MBU/04/2021. It becomes a factor that binds BUMN to measure these impacts. The Social Return on Investment (SROI) can be one of the methods to measure impacts. Eventually, the Minister of BUMN’s Regulation PER-5/MBU/04/2021 on the TJSL program became the foundation of CSR practices for state-owned companies which also became the ideal references of CSR practices in Indonesia.